The Impacts of a Civic Engagement Cohort Program for Water Quality Professionals. (19th September 2018) - Kallestad, Elizabeth; Chazdon, Scott; Bohn, Hannah
Abstract: In this article, researchers report the impact study results of University of Minnesota Extension's civic engagement for water quality cohort program. The cohort curriculum highlights Extension's research‐informed, five‐stage civic engagement model emphasizing process design and process management. Using a non‐random comparison group design, a survey was conducted with participants of three civic engagement cohorts for water quality professionals, as well as a comparison group of water quality professionals not part of a cohort. Survey results were aggregated into the five stages of Extension's civic engagement process: prepare, inquire, analyze, synthesize, and act together. Findings indicated cohort participants experienced significantly better results than members of the comparison group in four of the five stages. A strength of Extension's civic engagement model and curriculum is its emphasis on the collective nature and processual aspects of civic engagement work. Cohort participants received training on civic engagement skills, which are not often emphasized in education for water quality professionals. While both groups reported a high frequency of increased civic engagement skills, cohort participants did not report more frequent collaboration or public engagement behaviors than comparison group members. A challenge for those training water quality professionals is instilling the value of civic engagement skills in addition to the more traditional technical skill sets associated with water quality work. Additionally, ongoing training and organizational support is needed for practitioners to effectively implement new skills and leverage new networks.